CONCESSIVE NON-IMBEDDED CONSTRUCTIONS IN MACEDONIAN (Journal of Contemporary Philology, 2018)
The  paper  discusses  the  concessive  constructions  consisting  of  (verbal  and  qualifying) adjectives, nouns and verbal adverbs detached from the prosodic structure  of  the  utterance.  This  paper  focuses  on  several  properties  of  these  constructions: the information character and the position of the constructions, on the one hand, and the syntactic functions of the referents and their status regarding the opposition given vs. new information, on the other hand. The analysis  is  carried  out  on  examples  collected  from  literary  works  by  several  Macedonian writers.
Keywords: concession; non-embedded construction; information; referent; syntactic function